CLINICAL CHARACTERISTICS IN FEMALE CHILDREN WITH CONGENITAL ADRENAL HYPERPLASIA DUE TO 21-HYDROXYLASE DEFICIENCY UNDERGOING GENITAL RECONSTRUCTION SURGERY (Vietnam Journal of Community Medicine, 2026)
Objective: To describe some clinical characteristics of female children with congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency who underwent feminizing genitoplasty. Subjects and Methods: A retrospective descriptive study was conducted on 103 female patients with CAH due to 21-hydroxylase deficiency who underwent feminizing external genital reconstruction performed by the same surgeon between 2020 and 2025 at the National Children’s Hospital.Results: From January 2020 to December 2025, 103 female patients with CAH due to 21hydroxylase deficiency underwent feminizing external genital reconstruction by the same surgeon. 72% of patients were diagnosed during the neonatal period, predominantly presenting with the salt-wasting form. The simple virilizing form accounted for 28% of cases. The disease showed familial occurrence, with nearly one-quarter of patients having affected siblings. The mean age at surgery was 37 ± 35 months (range: 6–211 months). External genital abnormalities classified as Prader stages 2 and 3 were most common, accounting for 65% of cases. Severe forms with a high urogenital sinus (Prader stages 4 and 5) accounted for 25%.Conclusion: In female children, CAH due to 21-hydroxylase deficiency most commonly presents as the salt-wasting form, is typically diagnosed in the neonatal period, and most frequently manifests with Prader stage 2 or 3 genital abnormalities.
Keywords: congenital adrenal hyperplasia, genitoplasty, prader